A new species of the genus Synonychimorpha Miyatake (Coleoptera: Coccinellidae) from South India - Poorani, J. (Zootaxa, 2003)
A new species of the genus Synonychimorpha Miyatake (Synonychimorpha immaculata sp. nov.) is described from south India. Sticholotis chittagongi Vazirani is transferred to Synonychimorpha and Sticholotis rufolimbata Canepari is proposed as a new junior synonym. A key to the known species of the genus is given.